Assessing the Association between Participation in Extracurricular Activities and Delinquent Behavior among Justice‐Involved Young Men. (12th December 2020) - Simmons, Cortney; Kan, Emily; Simpkins, Sandra; Datta, Sachiko; Steinberg, Laurence; Frick, Paul J.; Cauffman, Elizabeth
Abstract : Extracurricular activities (ECAs) have been found to promote positive youth development and protect against misconduct and minor delinquency. However, little research has examined whether ECA participation predicts delinquency among at‐risk young men or considered how delinquent behavior, in turn, impacts ECA participation. This study examined extracurricular participation over three years in a sample of 1, 216 justice‐involved young men ( M age = 15.29). Approximately half of the sample participated in ECA each year. A cross‐lagged panel model was used to examine the bidirectional association between ECA participation and two types of delinquency, school misconduct and criminal offending. The results suggest that ECA participation did not consistently predict subsequent delinquency. Rather, justice‐involved young men who engaged in more delinquency were less likely to participate in ECAs.